(untitled) (Gaceta Técnica, 2017)
One of the key aspects of the teaching task is to keep up with the advances that continually come up in the areas in which they are experts; Aspect that at times for multiple reasons is not easy that is feasible. The updating in content, new technologies, as well as teaching and learning methodologies is required for the training of competent students capable of performing before their peers. This paper presents how the methodology of Project-Based Learning (ABP) applied in the subject "Underground Water" of the civil engineering program of the Universidad Centroccidental Lisandro Alvarado, promoted the exchange of information, training of students in the field of software used In the area, as well as cooperation for the study of real situations in the context of the Lara state aquifers in Venezuela.